Dr. Kirk Lozada — Deep Plane Facelift — Philadelphia - Lozada, Kirk (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Kirk Lozada, practicing in Philadelphia, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003020; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; philadelphia